Turning English Language Teaching into Service Learning: Transformative Education for Fourth Industrial Revolution - Fatema, Kaniz; Hossain, Md Mozaffor (FOSTER: Journal of English Language Teaching, 2023)
This research article means to academically elaborate the imperativeness of establishing a pragmatic convergence between English Language Teaching (ELT) and Service Learning (SL) as a worthwhile way of ensuring Transformative Education (TE) which, eventually, has a rewarding prospect of buttressing the ensuing as well as the currently-functioning Fourth Industrial Revolution (4IR). The researchers delineate some feasible models for incorporating service-learning into ELT arrangements at the program offering entity, and thereby, illustrate how these SL and ELT combinations might result in TE, and, somehow or other, instigate FIR.